A fair allocation approach to the ethics of scarce resources in the context of a pandemic: The need to prioritize the worst‐off in the Philippines. Issue 4 (23rd September 2020) - De Castro, Leonardo; Lopez, Alexander Atrio; Hamoy, Geohari; Alba, Kriedge Chlare; Gundayao, Joshua Cedric
Abstract: Using a fair allocation approach, this paper identifies and examines important concerns arising from the Philippines' COVID‐19 response while focusing on difficulties encountered by various sectors in gaining fair access to needed societal resources. The effectiveness of different response measures is anchored on addressing inequities that have permeated Philippine society for a long time. Since most measures that are in place as part of the COVID‐19 response are meant to be temporary, these are unable to resolve the inequities that have led to the magnitude of morbidity and mortality associated with the pandemic. These cannot improve the country's readiness to deal with pandemics and other emergencies in the future. Transition to a new normal recognizes the possibility that other infectious diseases could come and endanger our health security. Our pandemic experiences are proving that having an egalitarian society will serve the interests not only of disadvantaged sectors but also of everybody else, including the privileged. Response measures should thus take the opportunity to promote equity by giving importance to the concerns of the underprivileged and vulnerable while giving preference to initiatives that can be sustained beyond the period of the current pandemic.